Expressive Sayings of “Taste Delicious” by Indonesian Content Creators in Culinary Review Shows on YouTube Channel - Sonezza Ladyanna (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2022)
The development of impressions on the Youtube channel contributes to the development of language use both on social media and the wider community, including in expressive speech about taste. Therefore, this study aims to explain the expressive utterances of taste used by Indonesian content creators in culinary review shows on the Youtube channel. This research is descriptive research with a qualitative method. The data source is culinary reviews shown on the Youtube channel from Indonesian content creators with data in the form of expressive utterances about taste. Data analysis was carried out by describing lingual units containing expressive utterances about taste through sociolinguistic studies. Based on the results of the study, the expressive utterances about taste used by Indonesian content creators in culinary review shows on Youtube channels include mantap “perfect”, badabest, nggak ada obat “the best”, seger “fresh”, mantep poll, mantap “yummy”, dabest, parah “heavenly”, bold banget “very bold”, nampol. Gak ngotak “very delicious”, umami, seksi banget “very appetizing”, Ya Allah “Oh Allah”, and gila “crazy” in addition to enak, lezat, sedap, and nikmat “tasty”. Due to the dynamic nature of the language, the creative lingual units used by the community, both online and in conversations outside the network, should be documented to map language development.